2015
DOI: 10.1016/j.surfcoat.2014.11.032
|View full text |Cite
|
Sign up to set email alerts
|

The chemical resistance of nano-sized SiC rich composite coating

Abstract: profiling, which revealed that the intermixed layer did not change during the harsh etching except the removal of its thin surface layer containing less than 20% SiC. The etching rate of the intermixed layer is orders of magnitude lower than that for poly-Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Here the profile starts with SiC concentrations larger than 20%. One can conclude that the good chemical resistance needs a SiC concentration of at least 20%; these findings are in good agreement with the previously reported ones [10].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Here the profile starts with SiC concentrations larger than 20%. One can conclude that the good chemical resistance needs a SiC concentration of at least 20%; these findings are in good agreement with the previously reported ones [10].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the chemical resistance of the SiC rich intermixed layer is excellent if the SiC concentration is higher than 20% [10]. In all irradiation experiments reported above there were regions with SiC concentration larger than 20%.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations